Review of Geological Framework and Hydrocarbon Potential of the Banyumas Basin - Permana, Asep Kurnia; R. Setiawan; Marjiyono; G.M. Lucki Junursyah; Hidayat; D. Yurnaldi; E.Y.Patriani; A. Setiawan (Pusat Survei Geologi, 2024)
The presence of numerous oil and gas seeps along the Pamanukan-Cilacap Fault Zone of the Banyumas Basin. This indicate that the Banyumas Basin is an active petroleum system. However, oil and gas exploration in this area is complicated by extensive volcanic rocks from Paleogene to Recent Times. Thick volcanic covers are responsible for the poor seismic data quality and making subsurface imaging is difficult. Therefore, there is prospective sedimentary sequence beneath the volcanic rock as potential hydrocarbon resources in this basin. This review will focus on geochemical and geophysical approach. Geochemical analysis was used to reveal petroleum generation underneath the volcanic cover. The combined geophysical methods, i.e. gravity, magnetotelluric and passive seismic tomography were applied to image subsurface sedimentary thickness and geology structure in this area. Biomarker analysis of oil seeps from study area indicates that the oil generation in the Banyumas Basin was derived from Late Cretaceous to Eocene sedimentary rocks which deposited in fluvial to deltaic environment. The gravity data delineation analysis shows two sedimentary sub basins, Majenang Sub Basin and Citanduy Sub Basin, a relatively northwest to southeast trends, correlates with the regional structural trend. These sub basins were also well determined from magnetotelluric data. The passive seismic tomography method enhancing the sub surface image. The Vp, Vs and Vp/Vs ratios can identify the sedimentary layer under the volcanic rocks, as well as geological structure feature within the basin. The flower structure and anticline structure are well imaged and could be the potential structural trap in the Banyumas Basin. Thus, this new insight provides opportunities for further petroleum exploration in this area. Keyword: Geochemistry, Banyumas Basin, passive seismic tomography, hydrocarbon potential